PENINGKATAN KUALITAS MASYARAKAT DESA PEGUYANGAN KAJA MELALUI BUDAYA GOTONG ROYONG - Mirah Purnama Sari A.A Pt. Agung (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2023)
Kuliah Kerja Nyata (KKN) Program is carried out with the aim of growing awareness and empathy for Warmadewa University students towards the real problems faced by rural communities, and also to realize community welfare and educate the nation's life and to promote sustainable development. This KKN activity is located in Peguyangan Kaja Village, North Denpasar District, Denpasar City, Bali Province. Peguyangan kaja village office is located on Jl. North Ahmad Yani No. 456, Peguyangan Kaja, North Denpasar, Denpasar City. Kuliah Kerja Nyata-Pembelajaran Pemberdayaan Masyarakat (KKN-PPM) UNWAR in Peguyangan Kaja Village is Group 2 and consists of 30 students. The approach system used is direct observation and deliberation. The solutions provided by KKN-PPM UNWAR students are as follows: 1) participating in